Primary hyperparathyroidism: Should preoperative glandular location studies be performed? - Ruso, Luis; Santandreu, Jorge; Morelli, Raúl (Cirugía del Uruguay, 1997)
Biological diagnosis of certainty makes primary hyperparathyroidism (PHPT) an entity of surgical treatment even in asymptomatic forms.